The history after the death of art - Fernández Uribe, Carlos Arturo (Estudios de Filosofía, 1996)
In this article the end of art is studied by means oja relation between art and the history of art, and there are mentioned also its important theoretical and methodological effects on the historiography of art. Its purpose is to connect the assumed existence and development of disciplines related to art, such as the history of art, to what is as art. Nevertheless, the conceptual frame of art is not considered here merely as the result of a philosophical history. lt is thought to be determined as well by its historical condition and by certain concepts and realities.